Some explicit expressions concerning the Nadiradze formal group law - М. Бакурадзе (Bulletin of L.N. Gumilyov Eurasian National University. Mathematics, computer science, mechanics series, 2019)
This note provides some explicit expressions concerning the coefficient ring of the Nadiradze formal group law. The motivation is that the Nadiradze, the Buchstaber and the Krichever formal group laws are identical and the Krichever formal group law corresponds to the Krichever-H¨ohn general elliptic genus [1].